IDEOLOGI TAKFIRI MUHAMMAD AL-MAQDISI: Memahami Hubungan Beragama dan Bernegara Perspektif Maqāshid asy-Syarī‘ah - M. Hafidh Widodo (Living Islam: Journal of Islamic Discourses, 2018)
The term "kaafir" (infidel) has existed since the time of the Prophet Muhammad.  In the Koran, it is stated that kaafir is a person who does not believe that Allah Swt. as God Almighty, people who worship idols, and Ahl Kitab (Jewish and Christian). The meaning of this term then changed, not only aimed at non-Muslims but also addressed to Muslims themselves. Muhammad  al- Maqdisi accused kaafir of those who did bid'ah, for those who made laws and those who followed laws other than the laws of the Koran and al-Hadith—then the Law, the 1945 Constitution, and Pancasila included kaafir products. As a consequence, they have been considered apostates and truly have become non-Muslims, and their blood is halal to be killed. The question is "how did the takfiri ideological concept according to Muhammad al-Maqdisi relate to religion and state".